Analisis Penggunaan Partikel Akhiran Shuujoshi â€˜Neâ€™ dan â€˜Yoâ€™ Pada Novel â€œSabiru Kokoroâ€ - Manurung, Rudi Hartono (Humaniora, 2010)
Shuujoshi is a particle in the end of a sentence which shows speaker?s feeling and influence listener?s. Shuujoshi ne and yo have meaning differences as functional distinction that make the two articles divided into each functionalization. Using shuujoshi ne and yo is related with speaker?s consideration towards information of listener. It is noted that Shuujoshi ne, used by speaker when he has the same perception with listener. Meanwhile, using shuujoshi yo happens when there is different statements from speaker and listener?s perception. Besides, there is also meaning differences among shuujoshi ne and the like, and also among shuujoshi yo and the like. Therefore, when learners of Japanese language learn about shuujushi ne and yo, they will not rely on text books only.